A pirate ship sailed into the yacht club: How we built a novel pediatric emergency medicine curriculum for an emergency medicine training program. Issue 3 (31st July 2021) - Andrada, Emily; Danielson, Aaron; Magaña, Julia; Tzimenatos, Leah; Clarke, Sam
Abstract: Background: Pediatric emergency medicine (PEM) has seen little progression toward a standardized PEM educational framework. The 2018 Academic Emergency Medicine Consensus Conference on Advancing PEM Education addressed this gap in core EM education. Absent elements include a "broad needs assessment to identify and evaluate existing curricula and systems gaps in EM training" and a "clearly defined core PEM curriculum that unifies and drives the learning process." PEM education innovators were called to construct a "unified foundation in PEM education for all levels of emergency care" and to "promote innovation in teaching and learning strategies in curricula." We endeavored to meet this challenge at our institution. Methods: The PEM curriculum design is based on the Kern model of curriculum development and included a needs assessment, development of goals and objectives, educational strategies, implementation, evaluation, and programmatic feedback. We committed to using effective learning strategies and active learning methods in developing our curriculum and conducted a 1‐year pilot within our EM residency's didactic conference. We used exit surveys to collect feedback for each session as well as midyear focus groups to gauge the program's effectiveness. At the start and end of the pilot year residents completed the PEM survey regarding the effect of the PEM curriculum on their self‐assessed knowledge, training, and comfort in managing PEM topics. Results: Feedback regarding the PEM curriculum was positive. Following 1 year of the pilot curriculum, learners in the PGY‐1 and PGY‐3 classes demonstrated statistically significant improvement in their self‐assessed knowledge, training, and comfort with PEM topics. The PGY‐2 class had a similar statistically significant improvement in self‐assessed knowledge in PEM topics. Conclusions: Our novel PEM curriculum was well received and has shown early evidence of improving self‐assessed knowledge and comfort among EM residents.